Understanding African poverty over the longue durée: A review of Africa's development in historical perspective - McMillan, Margaret S. (American Economic Association, 2017)
The sixteen essays edited and synthesized by Emmanuel Akyeampong, Robert H. Bates, Nathan Nunn, and James A. Robinson contribute significantly to our understanding of the following questions: (1) When did Africa become poor?; (2) Why did Africa become poor?; and (3) Why has Africa remained poor? Although these questions are impossible to answer in a definitive way, the partial explanations offered in this book are insightful and thought provoking and are summarized in this article. However, they also rest primarily on economic and political arguments. The importance of geography, which is mostly not explored in these essays, is reviewed in the final section of this article. (JEL F54, I32, J11, N17, N37, N47, O10)